America's bank : the epic struggle to create the Federal Reserve - Lowenstein, Roger (Penguin Press, 2015)
Chronicles the tumultuous era and remarkable personalities that created the Federal Reserve, tracing the financial panic and widespread distrust of bankers that prompted the landmark 1913 Federal Reserve Act and launched America's first steps onto the world financial stage.